'Bring on the Dancing Horses!': Ambivalence and Class Obsession within British Media Reports of the Dressage at London 2012. (May 2013) - Fletcher, Thomas; Dashper, Katherine
Due to historical relationships with the military, royalty, landed gentry and upper-class society, equestrian sport faces regular accusations of being elitist and exclusionary. Through qualitative textual analysis of British press reporting of dressage events at the London 2012 Olympic Games we argue that despite British dominance of the sport, these historical associations with the upper classes, privilege and elitism were foregrounded in many media reports; trivialising and at times mocking dressage. We identify three key themes related to the ways in which media reports framed dressage and its participants in heavily class-laden terms. Faced with their ignorance of the sport, the majority of articles analysed resorted to class-based stereotypes that trivialised, satirised and devalued this seemingly elitist and incomprehensible sport. The success of Team GB in dressage meant that media reports were never wholly critical and elements of the hysteria and pride surrounding the Games led to a highly ambivalent response to dressage that reflects the 'vague, confused, contradictory [and] ignorant' (Cannadine 1998 : x) attitudes to social class that characterise British society at the current time.